The Impact of Product Innovation, Restaurant Atmosphere, and Promotion Strategies on Sales Performance: Evidence from Song Fa Bak Kut Teh Restaurant, Medan - Saragih, Meryanti; Harahap, Rifqah; Bako, Evi Novalin (Global Insights in Management and Economic Research, 2025)
Purpose of the study: The intensifying competition in the restaurant industry necessitates comprehensive marketing strategies to enhance sales performance. This study investigates the influence of product innovation, restaurant atmosphere, and promotional strategies on sales volume. This research aims to examine the partial and simultaneous effects of product innovation, restaurant atmosphere, and promotion on sales volume at Song Fa Bak Kut Teh Restaurant in Medan, Indonesia. Materials and methods: A quantitative approach was employed using incidental sampling to select 100 respondents from a population of 28,207 customers. Data were collected through structured questionnaires and analyzed using multiple linear regression analysis with SPSS version 25. Validity, reliability, normality, multicollinearity, and heteroscedasticity tests were conducted to ensure data quality. Results: The regression analysis yielded the equation Y = 4.231 + 0.213X₁ + 0.354X₂ + 0.098X₃. Product innovation (t = 2.318, p = 0.023), restaurant atmosphere (t = 4.615, p < 0.001), and promotion (t = 4.655, p < 0.001) demonstrated significant positive effects on sales volume. The simultaneous F-test (F = 36.443, p < 0.001) confirmed the collective influence of all independent variables. The adjusted R² value of 0.518 indicates that 51.80% of sales volume variance is explained by these three variables. Conclusions: Product innovation, restaurant atmosphere, and promotional strategies significantly contribute to sales performance both individually and collectively. Restaurant atmosphere emerged as the strongest predictor, followed by promotion and product innovation. Management should prioritize integrated marketing strategies encompassing continuous product development, atmospheric enhancement, and diversified promotional activities to optimize sales performance.